2017
DOI: 10.1097/rhu.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatologists Modestly More Likely to Counsel Smokers in Visits Without Rheumatoid Arthritis Control

Abstract: Background Among patients with rheumatoid arthritis (RA), smoking increases risk for severe RA and pulmonary and cardiovascular disease (CVD). Despite this, little is known about smoking cessation counseling by rheumatologists. Objectives We examined predictors of tobacco counseling in RA patients who smoke including the effect of perceived RA control. We hypothesized that patients with controlled RA would receive more counseling according to the competing demands model, which explains that preventive care g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…Smokers with chronic respiratory diseases did indeed receive smoking cessation support more often than smokers without diseases. It seems that the existence of chronic respiratory disease may increase physician engagement in cessation as smokers with respiratory disease received support more often than smokers with other chronic non-respiratory diseases, in accordance with other studies 16-18 . Smokers with respiratory disease may contemplate quitting smoking and therefore request advice and support from healthcare professionals more often than smokers without any diseases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Smokers with chronic respiratory diseases did indeed receive smoking cessation support more often than smokers without diseases. It seems that the existence of chronic respiratory disease may increase physician engagement in cessation as smokers with respiratory disease received support more often than smokers with other chronic non-respiratory diseases, in accordance with other studies 16-18 . Smokers with respiratory disease may contemplate quitting smoking and therefore request advice and support from healthcare professionals more often than smokers without any diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Current research suggests that physician assistance in smoking cessation (i.e. brief counseling and pharmacotherapy) may be increased among smokers with chronic diseases than smokers without diseases 16-18 . Amongst sociodemographic factors that have been found to influence smoking behavior and cessation assistance are age, income, and educational level 19-21 .…”
Section: Introductionmentioning
confidence: 99%
“…In a prior study, we also noted lower rates of incident hypertension diagnosis in RA patients than peers, with particularly low rates in RA patients who currently use tobacco [31]. In another study, we also reported that only 10% of encounters with RA patients who smoked documented cessation counselling[32] suggesting that competing priorities alone did not explain gaps in CVD risk factor counselling for either hypertension or smoking cessation. Likewise, noting more BP-communication after CVD events highlights a missed opportunity to reduce CVD by addressing modifiable risk factors like hypertension before events occur.…”
Section: Discussionmentioning
confidence: 70%
“…[10] In specialty clinics, however, clinicians discuss CVD risk factors such as BP or tobacco in only 10% of relevant specialty visits, despite routinely assessing them. [11,12] Non-vascular specialty clinics have not implemented protocols to address high BP and tobacco use, which are the most prevalent risk factors for CVD in US adults. In particular, although many rheumatology populations face increased in ammatory CVD risks, [13] rheumatologists typically consider addressing CVD risk factors to be outside their scope of practice.…”
Section: Introductionmentioning
confidence: 99%